ʿIllat Idraj and Examples of Hadiths - Agus Nurdianto; Iqdam Mauludi; Engkos Kosasih; Irwan Abdurrohman; Dede Rodliana (al-Afkar, Journal For Islamic Studies, 2026)
This paper discusses the concept of ʿIllat Idraj, one of the subjects in the science of hadith, which refers to a hidden defect involving the insertion of the narrator’s own wording into the text of a hadith, thus causing confusion between the narrator’s words and the original text of the hadith. Idraj constitutes a form of ʿillah that can undermine the quality of a hadith, rendering a narration that appears authentic to actually be weak upon deeper examination. This study explains the definition, classification, and impact of ʿIllat Idraj in determining the authenticity status of hadiths. Examples of hadiths with ʿIllat Idraj are provided to clarify this phenomenon. The method employed is library research, involving critical analysis of both the chain of transmission (isnad) and the content (matan). The findings indicate that understanding ʿIllat Idraj is crucial for verifying the quality of hadiths and for advancing scientific methodology in hadith research.